Implementasi Model Pembelajaran PBL dalam Meningkatkan Hasil Belajar Peserta Didik Kelas 4 pada Mata Pelajaran IPS Materi “Indonesia Kaya Budaya” SD N 2 brangkal. - Nova Sugiana Purwaningrum; Selvia Maharani; Isna Rahmawati (CV. ITTC INDONESIA, 2024)
Learning models are important in teaching and learning activities. Implementing the Problem Based Learning (PBL) learning model or problem-solving learning model is one way for educators to attract enthusiastic students to have more fun learning and understand the material. Including science and technology material using the PBL model is an effort by educators at SDN 2 Brangkal to be able to convey material that follows the Merdeka curriculum well. We conducted this research to improve the learning outcomes of grade 4 students at SDN 2 Brangkal using the PBL learning model in the science material Chapter 6